إسهام الصراع الإجابي بين الشرق والغرب في الرواية "إسمي أحمر" لأورهان باموق من خلال نظرية ليويس ألفريد جوسير - خطيب الأمم; عبد الباسط; أحمد خليل (Prosiding Konferensi Nasional Bahasa Arab, 2017)
Abstract: One of the novels with such an intrigue social conflict provided inside is the novel“Ismi Akhmar” written by Orhan Pamuk. The conflict is portrayed very interesting as it narrates the existence of different ideology of West and East found in the era of Sultan Murad III. West refers to the non-muslim Europeans, while East refers to the muslims. The conflict issues between West and East are actually a classic conflict occurred since long ago which keeps remaining up to this day. This is what basically inspires the researcher to analyse the conflict issue portrayed in the novel.This research uses theory of social conflict proposed by Lewis A. Coser which analyses the data indicating either individual or collective conflict. This study is projected to answer the research questions: (1) to portray the conflict of West and East in the novel “Ismi Akhmar”. (2) to describe the causes of the conflict, and (3) to describe the effects of conflict. This study employs descriptive qualitative research method. The method of data collection use reading and writing. For the way of data analysing use which is explained by Mills Habermann that conduct four steps, data collection, reduction, explaining, and conclusion. The result of the study reveals that: 1). Novel “Ismi Akhmar” attempts to interpret an ideological conflict between West and East on the paintings found in Turkey in the era of Sultan Murad III which causes the killings. 2). The causes of the conflict are four: turmoil, different ideology of the paintings, Ulama al Ardrumi’s provocation, and the death of Black Uncle. 3). There are some effects of the conflict as a causes, effects of turmoil, different ideology of the paintings, Ulama al Ardrumi’s provocation, and also effect of the death of Black Uncle. الكلمات الرئيسية: الصراع، الإيديولوجي، الغرب والشرق